A Prototype of Monitoring and Early Warning System of Public Water Flow Interference based on Arduino, Firebase Realtime DB, and Android - I Putu Arya Dharmaadi; Dewa Made Sri Arsa; Gusti Made Arya Sasmita (Jurnal Pekommas, 2021)
The majority of the population uses clean water sourced from the PDAM (Indonesian Regional Water Supply Company) pipeline to meet their daily needs. However, clean water utilization is sometimes not smooth because the upstream's water supply is stalled or the PDAM pipeline disrupted. This disruption that often occurs slowly causes routine community activities, such as bathing or cooking, become stop because clean water is a basic need. Thus, a system is needed to provide early warning when the PDAM water supply starts to have problems so that the community can make initial anticipation. This study designed a prototype of an early warning system using an Arduino-based water flow sensor that records water flow discharge data on the PDAM pipeline and sent to the Firebase Realtime Database to be monitored in real-time through an Android application. The system testing is done by black-box testing, i.e. we check all functions of this system, mainly on sending a warning notification when the water flow debt is at a low rate. In the end, by using this system, the user can prepare themselves early, such as collecting residual water debit in the tub and save water when there is a disruption in PDAM water.